Knowledge, attitudes and practices of intensive care unit physicians towards the management of acute respiratory distress syndrome in China: a cross-sectional survey - Jing Qian; Yinglin Wu; Xiaoqin Zhao; Zhidan Qin; Yongyi Meng; Mingjing Yin; Hanchun Wen; Juntao Hu; Zhanhong Tang (BMJ Open)
Objectives This study aimed to assess the knowledge, attitudes and practices (KAP) of intensive care unit (ICU) physicians in China towards acute respiratory distress syndrome (ARDS).Design A cross-sectional study was conducted between September and November 2022.Participants A total of 497 ICU physicians participated, with 258 (51.91%) being male and the majority aged 30–40 years (56.74%).Interventions Participants were surveyed to evaluate their KAP regarding ARDS, with mediation analysis employed to elucidate the association between demographic characteristics and KAP scores.Primary and secondary outcome measures The mean scores for KAP were 11.89±2.64 (range: 0–17), 44.73±4.85 (range: 12–60) and 18.26±3.43 (range: 1–48), respectively. Pearson correlation analysis showed positive correlations between knowledge and attitude (0.367), knowledge and practice (0.582) and attitude and practice (0.314) (all p<0.001).Results Mediation analysis indicated that attitude (β=0.07, p<0.001) and hospital type (β=−0.84, p=0.005) had direct effects on practice, while knowledge had significant direct (β=0.68, p<0.001) and indirect (β=0.03, p=0.019) effects. Additionally, education (β=0.47, p<0.001), work experience (β=0.25, p<0.001), hospital classification (β=−0.91, p<0.001), ICU type (β=−0.61, p=0.001) and ARDS experience (β=−1.57, p<0.001) showed various indirect effects on practice.Conclusions ICU physicians in China exhibited inadequate knowledge, moderate attitudes and suboptimal practices regarding ARDS management. Enhancing education and work experience is crucial, along with practical, scenario-based training, to improve KAP in ARDS management.